The cyclicality of interest rate spreads in Austria: Evidence for a financial decelerator? - Johann Burgstaller (Johannes Kepler University of Linz, Department of Economics, 2006)
This study explores an important aspect of how the Austrian banking sector contributes to the propagation of aggregate shocks. Time series data for the 1995-2003 period are applied to examine the cyclical variations in interest rate spreads. Differentials between interest rates on loans and savings are not found to shrink in economic upturns, so there is no financial mechanism emanating from bank markups that would entail an amplification of macroeconomic fluctuations. But also the evidence for Austrian banks dampening the business cycle (a financial de-celerator) is not striking as the increases of interest rate spreads after shocks in the growth rate of real GDP are practically small.
Keywords: E32; G21; 330; Interest rate spreads; business cycles; financial accelerator; impulse response analysis; Zinsstruktur; Volatilität; Spillover-Effekt; Konjunktur; Österreich